Ligand-rare-earth ion energy transfer in coordination compounds. A theoretical approach - Malta, O. L. (Elsevier B.V., 1997)
A theoretical approach to the energy transfer process that occurs between a ligand and a rare-earth ion in luminescent complexes is presented. A discussion on the energy transfer mechanisms involved and on the associated selection rules is made. Numerical estimates are also presented.
Keywords: rare earth; coordination compounds; energy transfer